Facilitating organizational criteria for the implementation of bloco k in the brazilian sped fiscal: a multidimensional analysis - Silva, Paulo Sergio da; Seleme, Robson; Zattar, Izabel Cristina (Brazilian Journal of Production Engineering, 2025)
The evolution of information technology has driven the growth of the global economy and improved government functions. In Brazil, the creation of SPED Fiscal - Block K in 2014 sought to ensure transparency and prevent fraud, but it brought challenges to companies, especially in adapting production processes, management systems (ERP) and employee training. This article aims to map organizational criteria that facilitate the implementation of Block K in logistics operations. To this end, a systematic literature review was conducted, analyzing 67 articles and identifying 242 success criteria related to ERP implementation. These criteria were refined with the help of the SCIPACE® platform and grouped into four categories (Organizational, Managerial, Technological and Functional) using the VOSViewer® software. Empirical validation was performed via a Likert questionnaire, with responses from 29 experts from 12 companies, reaching a return rate of 55%. The analysis revealed a 78% relationship index between the criteria and the functions of the digital supply chain. Three criteria were excluded due to low connectivity, consolidating 13 criteria, which form a structured model to support the efficient implementation of Block K.